Pengaruh Video Suport Terhadap Pengambilan Keputusan Wasit Futsal - Saputra, Mochamad Yamin; Nurcahya, Yudi; Kusumah, Widi (Fakultas Pendidikan Olahraga dan Kesehatan, Universitas Pendidikan Indonesia, 2023)
With the current development and advancement of technology, various types of high-tech auxiliary equipment have been gradually introduced into futsal matches to help referees officiate matches, starting with referee communication aids and now the introduction of Video Support. The Indonesian Pro Futsal League is adopting Video Support in the 2022/2023 competition season. The aim of this research is to find out an overview of the introduction of Video Support in futsal matches with the decision making of futsal referees. The method used in this research is a qualitative descriptive research method. This study is to find out what Video Support represents in the 2022/2023 futsal competition with percentages and a t test to determine the effect. The match variables that the researchers considered included: goals, penalties, yellow cards and red cards. The research results produced in this study were that for VS goals, the average score was 0.167, for yellow cards 0.227, for red cards 0.524, and for violations 0.102. In other words, the use of VS in pro futsal league matches has a good picture, especially in helping futsal referees in making decisions on the field. Meanwhile, to find out the effect, the results obtained showed that there was a significant influence of the use of video supports on the futsal referee's decision making in the field, with a calculated t test result of 8.544 t table 1.623. When the referee experiences problems in making decisions, especially in goals, yellow cards, red cards and undetected violations, the role of video support will help the referee in making better decisions.